Pengaruh Kompetensi, Penggunaan Teknologi Informasi, Komunikasi dan Sistem Pengendalian Internal Terhadap Kinerja Pegawai - Muhammad, Endang; Noch, Muhamad Yamin; Suratini, Suratini (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This research investigates the influence of competency, information technology usage, communication, and internal control system on employee performance within the Badan Pusat Statistik (BPS) of Papua Province. Using a quantitative approach, the study targets a population of 78 employees from BPS Papua Province. All employees were included in the study due to the population size being less than 100. Data collection involved primary data through Likert scale questionnaires. Statistical analyses included descriptive statistics, validity and reliability tests, classical assumption tests, and hypothesis testing through partial (t-test), simultaneous, and determination coefficient tests. The results indicate that competency, communication, and internal control system significantly affect employee performance, while information technology usage does not. Collectively, these variables demonstrate a significant impact on employee performance. Recommendations include continuous competency improvement through training, enhancing information technology infrastructure, fostering effective communication, and evaluating communication quality. Implementing these recommendations is expected to significantly enhance employee performance at BPS Papua Province, thereby contributing to organizational goals.